Intramuscular Myxoma, Mimicking a Psoas Abscess - A. A. Khairullin; M. N. Klimentov; D. N. Kuklin; S. V. Sysoyev (Неотложная медицинская помощь)
We report a clinical observation of intramuscular myxoma, mimicking a psoas abscess. Surgical minimally invasive treatment of the disease has been suggested. This clinical observation shows an example of the effective use of minimally invasive treatment methods in surgical practice, as an alternative to open surgery.